ANALISIS KINERJA KEUANGAN KOPERASI PEGAWAI NEGERI (KPN) MU’AMALAT KANTOR KEMENTERIAN AGAMA KOTA MAKASSAR - Chairul Ihsan Burhanuddin; Muhammad Nur Abdi (AkMen JURNAL ILMIAH, 2019)
This study aims to find out how the financial performance of civil service coorperatives (KPN) Mu’amalat the ministry of the city of Makassar. The analytical method used is descriptive quantitative analiysis method by using data collection technique that is research of library and field research consisting of method of documentation and interview method.From the results of research conducted on civil service cooperatives (KPN) Mu’amalat. Regarding the financial performance assessed from the liquidity ratio based on current ratio analysis shows very good figures, while the cash ratio shows poor results. The rentability ratio based on the analysis of economic rentability generated shows good figures, while the capital rentability analysis itself shows poor results. Further on the solvency ratio based on the analysis of debt to asset ratio and long term debt to equity ratio produced respectively indicate the numbers with very good criteria.